Przybrany ojciec. Czesław Miłosz w Chinach - Krenz, Joanna (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
Czesław Miłosz remains among the most important foreign authors and literary authorities for Chinese poets. Initially received in China with distrust and uncertainty, then portrayed in the official state discourse of romantic-revolutionary literature as the bard of socialism, Miłosz became the spiritual father of the younger generation affected by the Cultural Revolution and Tiananmen Square Massacre, a witness of the age, and a symbol of intellectual independence and resistance against totalitarianism. After a period of reading Miłosz in terms of ethical and political categories, Chinese reviews and literary texts in the 2010s and 2020s increasingly refer to Miłosz as philosophical and metaphysical poet. This article analyses Miłosz’s reception in China, paying attention to the historical, cultural, and linguistic factors that shaped the assimilation of his work and the values he brought to Chinese poetry.